A divisão do trabalho: do Iluminismo Escocês a Hegel (Revista Eletrônica Estudos Hegelianos, 2022)
“In modern political economy the division of labour is a main aspect”, says Hegel in one of his lectures on the Philosophy of Right, and he keeps this insight in mind in his own treatment of the division of labour. While some of his early reflections (during his years in Stuttgart and Tübingen) on the divided audience of poetry in the modern world, may be understood as taking position with regard to certain aspects or consequences of the division of labour, he did, at that time, not yet use the term Arbeitsteilung (division of labour) and it seems clear that his mature views on the issue did not emerge before his Jena years. It is not surprising that in manuscripts from that same period, Hegel mentions Adam Smith explicitly for the first time. This article begins by identifying what was original and innovative in the Scottish school’s (next to Adam Smith, Adam Ferguson and James Steuart are taken into account) treatment of the division of labour – (a) that it is seen as the decisive driving force behind economic development; (b) that it is discussed in the context of the most advanced technological and trading conditions of the time; and (c) that its advantages (e.g., higher productivity) are intrinsically linked to its drawbacks (social inequality and the dehumanizing, alienating effects) – and then compares each of these features with Hegel’s own discussion of the issue.